A three-dimensional Analysis of the Net Financial Results in Public Enterprises - Comporek, Michał; Shchyrba, Iryna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2023)
Objective: The paper aims to provide a diagnostic assessment of the net profits (losses) in international public companies listed in the WIG-CEE index from 2011–2020. Research Design & Methods: The quality of the reported earnings was illustrated by diversified coefficients of stability and smoothness of net profit (loss) and discretionary accruals, extracted by the Jones model based on the cash and balance sheet methods. Spearman’s rank correlation coefficient was used to assess the relationship between the tested variables. Findings: Strategies of intentionally lowering net financial results dominate the research sample. No statistically significant relationships were observed between the quality of net profit (loss) measures classified in separate generic groups. Implications / Recommendations: The results of empirical analyses reflect that the evaluation of the earnings quality of enterprises should be based on various economic measures, as the use of individual indicators may lead to erroneous evaluation. Contribution: The research may be important from the perspective of economic practice, looking for tools and instruments for predicting activities aimed at artificially shaping the financial result of enterprises.